THE BASIC PRINCIPLES OF ARMENIAN GEOLOGICAL DICTIONARY (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The scientific workers of historical and regional geology Department of Yerevan State University started working on the first Armenian Enciclopedia Dictionary of geological terms (about 6000 terms). Taking into account the importance of the problem in the item are written those basic principles, which are created by authors and will be used in compilation of the dictionary.
Keywords: Armenian Enciclopedia Dictionary of geological terms; historical and regional geology; Armenian Geological Dictionary